Possession adnominale dans différentes variétés de wolof - Voisin, Sylvie (AAeO - Afrikanistik-Aegyptologie-Online, 2021)
The aim of this article is to show the diversity of several varieties of Wolof, which are still little known and very poorly exploited, by showing clear differences between certain dialectal varieties, at the morphological and syntactic levels. The field in which this diversity will be dealt with is the adnominal possession through two structures: the possessive construction and the genitive construction. The description and comparison of these constructions in several varieties show quite important differences in the morphemes used or in the use of apparently identical morphemes leading to quite different rules of construction according to the dialects.